Kepraktisan LKPD “Aku Bisa Membaca dan Menulis” untuk Mengukur Literasi Dasar Siswa Slow Learner - Syifa Kifayatus Sa’diyah; Nurul Istiq’faroh; Dhini Dwi Permatasari (CV. Kurnia Grup, 2026)
Basic literacy is an essential competency that must be mastered by elementary school students. However, its development remains a challenge, especially for slow learners who have limitations in processing information. One factor that influences learning success is the availability of teaching materials that are appropriate to student characteristics. This study aims to describe the practicality level of the Student Worksheet (LKPD)